The demographic ageing of population in Bosnia and Herzegovina: causes and consequences - Kadušić, Alma; Suljić, Alija; Smajić, Nedima (Journal for Geography, 2016)
In this paper the age structure and the ageing population process in Bosnia and Herzegovina in the second half of the 20th century and the beginning of the 21st century is analyzed. The main reasons that caused changes in the age composition of the population and the population ageing in Bosnia and Herzegovina have been researched. The main causes of the population ageing in Bosnia and Herzegovina in the second half of the 20th century were primarily trends in fertility rates and secondarily trends in mortality rates. The economic growth of Bosnia and Herzegovina after World War II conditioned changes in the economic and educational structure of the population and with that the changes in the natural increase rates and migration balance. The war was the main cause of negative demographic changes in Bosnia and Herzegovina in the period from 1992 to 1995, and the post-war adverse socioeconomic, political and other circumstances have been the cause of negative demographic trends after 1995. The aim of this paper is to determine the level of population ageing in Bosnia and Herzegovina and the consequences this process could have on the demographic future of this country.
Keywords: demographic ageing; age structure; population; demographic changes; Bosnia and Herzegovina